Internal Limiting Membrane Peeling for Persistent Submacular Fluid after Successful Repair of Diabetic Tractional Retinal Detachment - Byung Ju Jung; Sohee Jeon; Kook Lee; Jiwon Baek; Won Ki Lee (Journal of Ophthalmology)
This study is for reporting the outcomes of internal limiting membrane (ILM) peeling on persistent submacular fluid (PSF) after otherwise successful pars plana vitrectomy (PPV) for diabetic tractional retinal detachment (TRD). In this retrospective case series, five consecutive patients (5 eyes) who exhibited PSF following successful repair of diabetic TRD were included. The second operation was performed to remove ILM. The area of ILM peeling was expanded up to the major vascular arcade. Only air tamponade was used. The median interval between the first PPV and the second PPV with ILM peeling was 4.8 months (range: 4–6 months). PSF resolved completely within one (2 eyes) or 2 months after ILM peeling. The median logMAR best-corrected visual acuity (BCVA) was improved from 1.00 (Snellen equivalent 20/200) to 0.70 (Snellen equivalent 20/100). In conclusion, wide ILM peeling is an effective treatment option for PSF subsequent to successful repair of diabetic TRD. ILM peeling might increase the elasticity of retina, thereby allowing the retina to flatten. This procedure can induce faster retinal reattachment in diabetic TRD involving the macula.